Melatonin improves learning and memory of mice with chronic social isolation stress via an interaction between microglia polarization and BDNF/TrkB/CREB signaling pathway - Bagheri, Sayna; Moradi, Kamyar; Ehghaghi, Elnaz; Badripour, Abolfazl; Keykhaei, Mohammad; Ashraf-Ganjouei, Amir; Dehpour, Ahmad Reza (Elsevier, 2021)
Chronic social isolation stress (SIS) could impair learning and memory-related behaviors. Herein, we investigated the efficacy of Melatonin in treatment of memory despair and also its possible underlying mechanism of action in an animal model of SIS. For this purpose, mice were allocated to two opposing conditions, including social condition (SC) and isolated condition (IC), for five weeks. The study consisted of three groups, including salinetreated SC, saline-treated IC, Melatonin-treated IC (10 mg/kg/day for five successive days). At the end of the isolation period, mice underwent three neurobehavioral tests: passive avoidance (PA), Morris water maze (MWM), and Y maze (YM) tests. Hippocampus samples were obtained and the expressions of BDNF, TrkB, phosphorylated TrkB (pTrkB), CREB, phosphorylated CREB (pCREB), as well as M1 and M2 microglia were assessed. Interpreting the behavioral tests, we found that isolated mice showed lower freezing response in the PA test, lower number of novel arm visits in the YM, and higher escape latency and less time spent in the target quadrant in the MWM, when compared to SC rodents (P values < 0.001). The isolated group had higher M1/M2 relative ratio (P < 0.001), as well as lower concentrations of BDNF mRNA (p < 0.001) and protein (P < 0.001), TrkB protein (P = 0.035), CREB mRNA (P < 0.001) and protein (P = 0.012), pTrkB (P < 0.001), and pCREB (P = 0.035). However, Melatonin relatively reversed the behavioral, cellular, and molecular effects of SIS. Taken together, melatonin therapy could alleviate memory impairment through switching microglial polarization from M1 to M2 phenotype along with altered expression and function in the BDNF/TrkB/CREB signaling pathway.
Keywords: BDNF; Melatonin; Memory; Social isolation stress